2014
DOI: 10.1161/strokeaha.113.002745
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mural Cells Leads to Wall Degeneration, Aneurysm Growth, and Eventual Rupture in a Rat Aneurysm Model

Abstract: Background and Purpose— The biological mechanisms predisposing intracranial saccular aneurysms to growth and rupture are not yet fully understood. Mural cell loss is a histological hallmark of ruptured cerebral aneurysms. It remains unclear whether mural cell loss predisposes to aneurysm growth and eventual rupture. Methods— Sodium dodecyl sulfate decellularized and nondecellularized saccular aneurysm from syngeneic thoracic aortas were transplanted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 31 publications
2
106
0
Order By: Relevance
“…Clinical experience and experimental evidence have shown that the loss of mural cells is associated with an inability to transform intraluminal thrombus to stable scar tissue because of the lack of smooth muscle cells inside the wall. 28 Subsequently, the lack of thrombus organization is likely to be related to cellular loss of the sick wall in our GFAs.…”
Section: Discussionmentioning
confidence: 92%
“…Clinical experience and experimental evidence have shown that the loss of mural cells is associated with an inability to transform intraluminal thrombus to stable scar tissue because of the lack of smooth muscle cells inside the wall. 28 Subsequently, the lack of thrombus organization is likely to be related to cellular loss of the sick wall in our GFAs.…”
Section: Discussionmentioning
confidence: 92%
“…The saccular aneurysms to be decellularized before use in thrombus-induced decellularized aneurysms and thrombus-induced decellularized smooth muscle cell-transplanted aneurysms groups were processed as described in detail previously. 10,11 Briefly, donor grafts were harvested and frozen in PBS at −4°C. The next day the grafts were thawed, incubated for 10 hours at 37°C in 0.1% sodium dodecyl sulfate (SDS), and finally refrozen until use.…”
Section: Aneurysm Model Graft Decellularization and Thrombus Inductionmentioning
confidence: 99%
“…Existing protocols for high-resolution time-of-flight MRA 12 and CE-MRA 11 were performed. CE-MRA were analyzed and scored for the rate of thrombosis as described previously, with slight modification ( Figure IV in the online-only Data Supplement) 11,13 : 0=no recurrence (no filling); 1=partial recurrence (<50% filling); and 2=complete recurrence (>50% filling). Growing aneurysms were further analyzed using 3-dimensional active contour segmentation software itk-SNAP (V2.4, Pennsylvania, PA).…”
Section: Mri and Angiographic Evaluationmentioning
confidence: 99%
“…With the exception of a single case significant growth or dilatation of the experimental aneurysms was not observed and none of them ruptured 3 . However, if the harvested grafts are decellularized the aneurysms demonstrate a heterogeneous pattern of thrombosis, recanalization, growth, and eventual rupture 11 . Growing aneurysms in the latter study demonstrated marked adventitial fibrosis and inflammation, complete wall disruption, and increased neutrophil accumulation in unorganized intraluminal thrombus.…”
Section: Discussionmentioning
confidence: 99%